2016
DOI: 10.1007/s10329-016-0576-5
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of hermit crabs from their shells by white-faced capuchin monkeys (Cebus capucinus)

Abstract: We observed two capuchin monkeys (Cebus capucinus) feeding on hermit crabs (Coenobita compressus) on the coast, and the tactics they used to extract this well-protected prey. The observations took place during the dry season at Playa Escondida beach, Puntarenas, Costa Rica. The capuchins descended from trees at the back edge of the beach to capture passing hermit crabs. Both capuchins extracted the hermit crabs from their protective shells by holding the shell with one hand and pulling the crab out with the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…We have yet to find any evidence of stone tool use on the coasts of Coiba or Ranchería (figure 1), but surveys are still underway. Further, many of the resources which capuchins on Jicarón process using stone tools are available to and eaten by other white-faced capuchin populations including hermit crabs [118], halloween crabs (B. Barrett 2017, personal observation), marine snails and coconuts [37]. Fleshy exocarps of T. catappa are consumed by other capuchin groups across Coiba National Park and in Costa Rica [119]—however, capuchins are unable to access the nutritious endocarps without tools.…”
Section: Discussionmentioning
confidence: 99%
“…We have yet to find any evidence of stone tool use on the coasts of Coiba or Ranchería (figure 1), but surveys are still underway. Further, many of the resources which capuchins on Jicarón process using stone tools are available to and eaten by other white-faced capuchin populations including hermit crabs [118], halloween crabs (B. Barrett 2017, personal observation), marine snails and coconuts [37]. Fleshy exocarps of T. catappa are consumed by other capuchin groups across Coiba National Park and in Costa Rica [119]—however, capuchins are unable to access the nutritious endocarps without tools.…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, site preservation might have an impact on the visibility of tool-use but it is unlikely to obliterate all signs of such behavior. Further, many of the resources which capuchins on Jicarón process using stone tools are available to and eaten by other white-faced capuchin populations including hermit crabs (Soley et al, 2017), Halloween crabs (B. Barrett, personal observation), marine snails and coconuts (Méndez-Carvajal and Valdés-Díaz, 2017).…”
mentioning
confidence: 99%
“…These observations might be expected when predation is difficult and high‐risk, requiring speed, coordination and dexterity (Gunst et al, 2008; Gunst, Boinski, et al, 2010; Gunst, Leca, et al, 2010; Stone, 2006; Westergaard et al, 1997). Soley et al (2017) reported greater success with a hard‐to‐process resource with painful defence capacity (hermit crabs) for C. capucinus . In this context, it is interesting to note that the high‐risk, high‐speed attacks on Chartergus require experience and coordination, yet in no case was another animal seen observing the raider.…”
Section: Discussionmentioning
confidence: 99%